The influence of Sn particle incorporation on the photocatalytic activity of sprayed ZnO−SnO2 nanocomposites - S. Mahjoubi; M. Mezyen; G. El Fidha; N. Bitri; E. Llobet (Scientific Reports)
Abstract This paper investigates the photocatalytic performance of ZnO−SnO2 nanocomposites deposited using the Spray Pyrolysis technique, with varying percentages of tin oxide (20, 60, and 80%) on glass substrates at 350 °C. Comprehensive characterization of the samples was carried out using X-ray diffraction (XRD), Scanning Electron Microscopy (SEM), Atomic Force Microscopy (AFM), and UV–Vis spectroscopy to analyze their structural, morphological, and optical properties. The XRD analysis confirmed the hexagonal structure of zinc oxide and the tetragonal phase of tin oxide in the nanocomposites. The average crystallite size was found to decrease with an increase in the percentage of tin oxide. The UV–Vis spectra demonstrated that the band gap energy of the ZnO−SnO2 nanocomposite increased from 3.29 to 3.64 eV as the amount of Sn increased. The Urbach energy decreases reflecting an improvement in the structural and electronic quality of the material, with fewer defects and better crystallinity. Additionally, The SEM results reveal a transition in surface morphology with increasing Sn content, shifting from a smooth, compact structure to a highly aggregated particle surface, with the highest thickness (740 nm) observed at 80% SnO2. Remarkably, the ZnO−SnO2 nanocomposite with 80% tin exhibited superior photocatalytic activity, successfully degrading 91% of methylene blue solution within 180 min under UV irradiation. Moreover, the stability and reusability of the sample were demonstrated through repeated photocatalytic cycles. The use of a chemical synthesis technique for the elaboration of the Sn:Zn mixed nanocomposite and UV light as catalyzer which, is well suited for large bandgap materials, optimizes this work by providing an increased contact surface area and facilitating the interaction between the photocatalyst and the target molecules. These findings highlight its potential for effective environmental applications, specifically in photocatalysis for pollution control and environmental protection. The results collectively suggest that ZnO−SnO2 nanocomposites, deposited through the spray method, represent promising candidates for advancing photocatalytic technologies.